A new species of Urocopitid land snail from Haiti and a discussion of the genus Autocoptis (Gastropoda: Urocoptidae) - Thompson, Fred G. (Revista de Biología Tropical, 2012)
Autocoptis paulsoni n. sp. is described from Haiti. It is characterized by its large size, its cylindricaltapered shape, its fine costate sculpture on the teleoconch, a distinct but weak circum basal keel and its abbreviate conical juvenile shell. It is most similar to Autocoptis gruneri (Dunker 1844), which is redescribed, and its distribution is reviewed. The taxonomic status of the genus Autocoptis Pilsbry 1902 and its subgenus Urocoptola Clench, 1 935 are reviewed. The genus is endemic to Hispaniola and satellite islands.